Pengaruh Store Enviroment Quality Terhadap Perceived Legitimacy Dan Customer Shopping Behavior Di Matahari Departemen Store Tunjungan Plaza Ssurabaya - Budiman, Simplisius Holly; Lindawati, Tuty; Rahmawati, Veronika (Kajian Ilmiah Mahasiswa Manajemen, 2017)
The development of modern technology has an impact on life that is becoming more practical, fast and economical. Along with the development of these technologies, the existence of modern retail business becomes increasingly important because of the shift in spending patterns of people who prefer to shop in modern retail markets such as minimarkets, supermarkets or hypermarkets. The population of this study are consumers aged 17 years and over and have been shopping at Matahari Department Store Tunjungan Plaza Surabaya. Sampling used in this research is nonprobability sampling and the taking of the sample using incidental sampling technique. The sample was 110 respondents ie men and women. Data collection is done by distributing questionnaires. Data analysis technique used in this research is SEM (Structural Equation Model). Test results show that Store Environment Quality has an influence on Perceived Legitimacy; Perceived Legitimacy has an effect on Shopping Behavior, and Store environment Quality influence to Shopping Behavior, through Perceived Legitimacy mediation.